ACCESSIBILITY TO CENTER BUSINESS DISTRICT AND LAND PRICE - Suparmono Suparmono (Economic Journal of Emerging Markets, 2012)
AbstractThis paper models land price for housing in Sleman district. It uses a multiple regression model to estimate the land price based on various variables. It finds six variables that influence the land price, namely the land width, width of the nearest road, width of the nearest main road, distance to the nearest main road, distance to Yogyakarta ring road, and the travel time to Gadjah Mada University campus. It also finds four insignificant variables, namely distance to Malioboro road, distance to Gadjah Mada University campus, travel time to Yogyakarta ring road, and travel time to Malioboro. Keyword: Land price, center of business district, accessibilityJEL classification numbers: D46, D49AbstrakPaper ini memodelkan harga tanah untuk perumahan di Kabupaten Sleman menggunakan model regresi berganda untuk memperkirakan harga tanah berdasarkan berbagai variabel. Paper ini menemukan enam variabel yang mempengaruhi harga tanah, yaitu lebar tanah, lebar jalan terdekat, lebar jalan utama terdekat, jarak ke jalan utama terdekat, jarak ke jalan lingkar Yogyakarta, dan waktu perjalanan ke Universitas Gadjah Mada. Paper ini juga menemukan empat variabel yang tidak signifikan, yaitu jarak ke jalan Malioboro, jarak ke kampus Universitas Gadjah Mada, waktu tempuh ke jalan lingkar Yogyakarta, dan waktu tempuh ke Malioboro.Keyword: Harga tanah, center of business district, aksesibilitasJEL classification numbers: D46, D49